2022
DOI: 10.3390/medicina58101319
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Bioinformatics Analysis of Crucial Gene of Heart Failure and Atrial Fibrillation Based on GEO Database

Abstract: Background and objectives: In clinical practice, we observed that the prognoses of patients with heart failure and atrial fibrillation were worse than those of patients with only heart failure or atrial fibrillation. The study aims to get a better understanding of the common pathogenesis of the two diseases and find new therapeutic targets. Materials and Methods: We downloaded heart failure datasets and atrial fibrillation datasets from the gene expression omnibus database. The common DEGs (differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Zhuang et al found that five genes, FRZB , SFRP4 , ETNPPL , AQP4 , and C1orf105 , were highly co‐expressed in AF and HF patients through transcriptome data analysis. 22 In this study, we found four new biomarkers highly correlated with AF and HF, namely, GLUL , NCF2 , S100A12 , and SRGN , which is different from the results of Zhuang et al Proteins encoded by GLUL belong to the glutamine synthase family and play a role in acid–base homeostasis, cell signalling, and cell proliferation. The DEGs associated with HF identified by Boyang et al through analysis of the Omnibus database included GLUL .…”
Section: Discussioncontrasting
confidence: 99%
“…Zhuang et al found that five genes, FRZB , SFRP4 , ETNPPL , AQP4 , and C1orf105 , were highly co‐expressed in AF and HF patients through transcriptome data analysis. 22 In this study, we found four new biomarkers highly correlated with AF and HF, namely, GLUL , NCF2 , S100A12 , and SRGN , which is different from the results of Zhuang et al Proteins encoded by GLUL belong to the glutamine synthase family and play a role in acid–base homeostasis, cell signalling, and cell proliferation. The DEGs associated with HF identified by Boyang et al through analysis of the Omnibus database included GLUL .…”
Section: Discussioncontrasting
confidence: 99%
“…The enrichment of the functions of the selected DEGs was performed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis with the cluster profiler package in R ( 22 ).…”
Section: Methodsmentioning
confidence: 99%